External quality assessment for laboratories in pan-India ILI/SARI surveillance for simultaneous detection of influenza virus and SARS-CoV-2 - Potdar, Varsha; Vijay, Neetu; Vipat, Veena; Jadhav, Sheetal; Gupta, Nivedita; Aggarwal, Neeraj (Frontiers in Public Health, 2023)
The Indian Council of Medical Research has set-up a nationwide network of 28 laboratories for simultaneous surveillance of influenza virus and SARS-CoV-2 in ILI/SARI patients, using an in-house developed and validated multiplex real-time RTPCR assay. The aim of this study was to ensure the quality of testing by these laboratories by implementing an external quality assessment program (EQAP). For this EQAP, a proficiency test (PT) panel comprising of tissue-culture or egg grown influenza virus and SARS-CoV-2 was developed. The PT panel was distributed to all the participant laboratories, which tested the panel, and submitted the qualitative results online to the EQAP provider. The performance of the laboratories was evaluated on qualitative criteria but cycle threshold (Ct) values were also gathered for each sample. On a qualitative basis, all the laboratories achieved the criteria of 90% concordance with the results of the PT panel provider. Ct values of different samples across the laboratories were within ≤ ±3 cycles of corresponding mean values of the respective sample. The results of this EQAP affirmed the quality and reliability of testing being done for simultaneous surveillance of influenza virus and SARS-CoV-2 in India.